The Effect Of Feeding Frequency and Feeding Rate On Growth, Feed Eficiencyand Survival Rate Of Java barb Larvae (Puntius JavanicusBlkr) - Betti Suryati Munthe; Hamdan Alawi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractResearch on the effect of feeding frequency and feeding rate on growth, feed eficiency and survival rate of java barb larvae (Puntius javanicus Blkr) was conducted on 26 June-4 August 2018 at the Fish Hatchery and Breeding, Pinang Mancung Tebing Tinggi, North Sumatra. In this research the larvae were rearing in aquarium sized 40x30x30 cm filled with 15 L of water. Each aquarium was stocked two larvae per L.The experimental design useda completely randomized design (CRD) with two factors, namely feeding frequency with three levels: two times/day (F2), three times/day (F3) and four times/day (F4). The second factor was the feeding rate with three levels: P25 (25 %of body weight), P50 (50 % of body weight), P75 (75 % of body weight).To minimize errors, each level of treatment was repeated 3 times. The best growth rate in the treatment of F4P75 (feeding frequency four times/day with feeding rate 75% of body weight)with an absolute weight of 2.45 gr, absolute length 3.45 cm, average growth rate of 14.78 %/day, feed eficiency 24.56 % and survival rate 98.88 %. The condition of water quality is the water temperature 24,6-27,90C, pH 5,3-6,7 and dissolved oxygen 5,1-6,0 mg/l. Keywords : Puntius javanicus Blkr, feeding frequency, feeding rate, growth, feed eficiency, survival rate.